1971
DOI: 10.1136/bjo.55.12.856
|View full text |Cite
|
Sign up to set email alerts
|

Injury to the eye by the sap of Euphorbia royleana.

Abstract: The saps of some plants are known to be highly irritant to the eye. We have recently seen a patient in whom accidental splashing with the sap of Euphorbia royleana caused acute bilateral conjunctivitis with corneal ulceration and iridocyclitis. Euphorbia royleana

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Euphorbia latex is cathartic, anthelmintic and used for a variety of conditions such as skin and eye diseases and snakebite (Chopra et al 1958, Basak et al 2009. The latex of Euphorbia royleana produces an intense conjunctival, corneal and iritic inflammatory reaction (Sood et al 1971). Significant antiarthritic activity has been observed in subacute and chronic models of formaldehydeinduced arthritis, adjuvant-induced developing and established arthritis (Bani et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Euphorbia latex is cathartic, anthelmintic and used for a variety of conditions such as skin and eye diseases and snakebite (Chopra et al 1958, Basak et al 2009. The latex of Euphorbia royleana produces an intense conjunctival, corneal and iritic inflammatory reaction (Sood et al 1971). Significant antiarthritic activity has been observed in subacute and chronic models of formaldehydeinduced arthritis, adjuvant-induced developing and established arthritis (Bani et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…tirucalli. [ 451112] Only one case of ocular toxicity with E. trigona was reported earlier by Scott et al [5] and they reported only corneal epithelial defect without edema and anterior chamber reaction. But in our Case 1, there was gross corneal edema with moderate anterior uveitis and secondary elevated IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Epiphora, lid swelling, photophobia, chemosis, and anterior-chamber inflammation were also common. [2][3][4][5][6][7][8][9][10][11] Symptoms generally worsened several hours to days after exposure. Final visual acuity was 6/6 in many cases.…”
Section: Discussionmentioning
confidence: 99%